Morbidity and mortality in long-term survivors of Hodgkin lymphoma: a report from the Childhood Cancer Survivor Study - Castellino, Sharon M; Geiger, Ann M; Mertens, Ann C; Leisenring, Wendy M; Tooze, Janet A; Goodman, Pam; Stovall, Marilyn; Robison, Leslie L; Hudson, Melissa M (Blood, 2011)
The contribution of specific cancer therapies, comorbid medical conditions, and host factors to mortality risk after pediatric Hodgkin lymphoma (HL) is unclear. We assessed leading morbidities, overall and cause-specific mortality, and mortality risks among 2742 survivors of HL in the Childhood Cancer Survivor Study, a multi-institutional retrospective cohort study of survivors diagnosed from 1970 to 1986. Excess absolute risk for leading causes of death and cumulative incidence and standardized incidence ratios of key medical morbidities were calculated. Cox regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) of risks for overall and cause-specific mortality. Substantial excess absolute risk of mortality per 10,000 person-years was identified: overall 95.5; death due to HL 38.3, second malignant neoplasms 23.9, and cardiovascular disease 13.1. Risks for overall mortality included radiation dose ≥ 3000 rad ( ≥ 30 Gy; supra-diaphragm: HR, 3.8; 95% CI, 1.1-12.6; infradiaphragm + supradiaphragm: HR, 7.8; 95% CI, 2.4-25.1), exposure to anthracycline (HR, 2.6; 95% CI, 1.6-4.3) or alkylating agents (HR, 1.7; 95% CI, 1.2-2.5), non-breast second malignant neoplasm (HR, 2.6; 95% CI 1.4-5.1), or a serious cardiovascular condition (HR, 4.4; 95% CI 2.7-7.3). Excess mortality from second neoplasms and cardiovascular disease vary by sex and persist > 20 years of follow-up in childhood HL survivors.